ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI PADI DI KELURAHAN LAMBANAPU KECAMATAN KAMBERA - Yulensi Konga Wandal; Adrianus Kabubu Hudang; Karolina Albina Rewa (Bajang Institute, 2025)
This study aims to analyze the factors influencing the income of rice farmers in Lambanapu Village, Kambera District. The variables examined include land area, selling price, production volume, and production costs. This research employs a quantitative method with an associative approach, involving 50 respondents selected through purposive sampling. Data were collected through observation and questionnaires, and analyzed using binary logistic regression. The results indicate that the regression model is appropriate for use. Simultaneously, the four independent variables do not have a significant effect on farmers’ income. However, partially, land area, selling price, and production volume show significant effects, while production costs do not influence income. These findings highlight that improving farmers’ income is more strongly driven by expanding cultivated land, stabilizing selling prices, and increasing production volume. Therefore, these factors should receive greater attention in efforts to enhance the welfare of rice farmers in Lambanapu Village